Explaining unexplainable food choices. (15th November 2017) - Adriaanse, Marieke A.; Kroese, Floor M.; Weijers, Jonas; Gollwitzer, Peter M.; Oettingen, Gabriele
Abstract: In recent years, psychologists have started to investigate the downstream consequences of nonconsciously activated behaviour (acting in an 'explanatory vacuum'). Results have shown that when such behaviour is norm‐violating, people experience a need to confabulate reasons for this behaviour. The present paper aims to add more convincing evidence for this assumption. Study 1 addresses this question by replicating Study 2 of Adriaanse, Weijers, De Ridder, De Witt Huberts, and Evers (2014 ) while adding a condition in which people are post hoc provided with an explanation for their behaviour. Study 2 addresses this question by explicitly demanding an explanation for a nonconsciously steered choice. Both studies were conducted in the context of eating behaviour. Results of both studies were indicative of confabulation as a downstream consequence of nonconsciously steered eating behaviour (Study 1) or food choice (Study 2). Future research should address the potential of confabulated reasons spilling over to next occasions.